Ethnomathematics: Concept of Transformation Geometry in Sasambo Batik Motifs Bale Lumbung Sasak - Heri Sopian Hadi; M Gunawan Supiarmo; M Qomari Hidayat; Lalu Ajimuliardi A (Jurnal Pendidikan Matematika Raflesia, 2022)
The research method used is qualitative research with an ethnographic approach. This purpose aims to explore the existence of mathematical concepts, especially the transformation geometry material in Sasambo Sasak batik. Then describe the transformation concepts contained in the batik. Researchers dig up information through observation, literature, and interviews with batik-related craftsmen to obtain accurate information. Respondents in this study were determined by the purposive sampling method. The selected respondents are Sasambo batik craftsmen. The results showed that there are geometric transformation concepts in the Sasambo Bale Lumbung Sasak batik motif, including translation, reflection, dilation, and rotation.